2021
DOI: 10.1093/icc/dtab006
|View full text |Cite
|
Sign up to set email alerts
|

Sources of inflation and the effects of balanced budgets and inflation targeting in developing economies

Abstract: This article presents a model in which distributional conflict and cross-sectoral interactions between demand and supply side forces determine inflation in developing countries. We show that the standard macroeconomic policy recommendations of inflation targeting and balanced budgets (i) increase volatility by amplifying external shocks and (ii) can lead to premature deindustrialization. The recent Brazilian experience is used to illustrate the argument.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The exclusion of aggregate demand issues -the potential for realization crisis, using Marxian terminology -represents a serious limitation of the analysis. Like their mature counterparts, developing economies may be subject to Harrodian instability, with another important source of instability coming from the external sector and the domestic policy response to external shocks (Martins and Skott 2021). These issues are beyond the scope of this paper, which has had a more limited purpose: to examine Goodwinian specifications of wage setting and their application to mature and dual economies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exclusion of aggregate demand issues -the potential for realization crisis, using Marxian terminology -represents a serious limitation of the analysis. Like their mature counterparts, developing economies may be subject to Harrodian instability, with another important source of instability coming from the external sector and the domestic policy response to external shocks (Martins and Skott 2021). These issues are beyond the scope of this paper, which has had a more limited purpose: to examine Goodwinian specifications of wage setting and their application to mature and dual economies.…”
Section: Discussionmentioning
confidence: 99%
“…Equation (Goodwin wage 1) could be extended to include an effect of profit shares on target real wages. 11 Similar specifications have been used by Skott (2005) and Martins and Skott (2021).…”
Section: Endogenous Normsmentioning
confidence: 99%
“…While acknowledging the initial success of inflation targeting, it has been suggested that inflation-forecast targeting is an approach more compatible with the mandate of sustainable price stability, which largely means reducing the price uncertainty about long-term price levels. This approach is perceived as difficult for developing countries, even if most have opted for the objective of price stability (or a targeting regime), they experience qualitative macroeconomic volatility, masked by quantitative stability, that is, their stability is only temporary and on a razor's edge, in reality whenever there is a small shock, this stability sees itself mechanically unbalanced (Heintz and Ndikumana, 2011;Morozumi et al, 2020;Cachanosky and Mazza, 2021;Martins and Skott, 2021).…”
Section: A Look At Developing Economiesmentioning
confidence: 99%